The effect of quality of implementation of pjj pjokc conditions, and achievement motivation on the students' learning outcomes of sma negeri 25 jakarta (during the covid-19 pandemic) - Daud Benny Simamora; Nofi Marlina Siregar; Yasep Setiakarnawijaya (UNIVERSITAS NEGERI JAKARTA POSTGRADUATE OF PHYSICAL EDUCATION DEPARTMENTS, 2022)
This study aims to determine the effect of independent variables on the dependent variable. Judging from the title of the thesis, there are three independent variables, namely the quality of PJJ PJOK, socio-economic conditions, achievement motivation. As the dependent variable is the learning outcomes of Physical Education students at SMA Negeri 25 JAKARTA. To determine the extent of the influence of the quality of PJJ PJOK, socio-economic conditions, achievement motivation on learning outcomes of PJOK students of SMA Negeri 25 Jakarta. This research was conducted at SMA Negeri 25 Jakarta, Central Jakarta. The research was conducted using descriptive research methods with a quantitative approach. Descriptive research method is a method used to solve problems that exist in the present. Investigations in this method using interview techniques, questionnaires, observation. It can also use test techniques, case studies, cooperative or operational studies. Descriptive method is designed to gather information about real conditions now (while taking place). The main objective in using this method is to create descriptive, systematic, factual and accurate description of the facts, properties and relationships of the phenomena being investigated.Samples were taken as many as 85 people, namely students of SMA Negeri 25 Jakarta. The sampling technique used was the Slovin technique and the data collection method used a questionnaire. Data analysis used descriptive analysis and path analysis.The results of this study indicate that; (1) There is no direct influence between the quality of PJJ PJOK on Achievement Motivation for students of SMA Negeri 25 Jakarta, this is evidenced by a significance value of more than0.05 (0.873> 0.05); (2) There is a direct influence between the Socio-Economic Conditions on Achievement Motivation in SMA Negeri 25 Jakarta, this is evidenced by a significance value less than 0.05 (0.047 <0.05); (3) There is a direct influence between the quality of PJJ PJOK on learning outcomes for students at SMA Negeri 25 Jakarta, this is evidenced by a significance value less than 0.05 (0.004 <0.05); (4) There is no direct influence between socio-economic conditions on learning outcomes for students of SMA Negeri 25 Jakarta, this is evidenced by the significance value obtained greater than 0.05 (0.564> 0.05); (5) There is no direct influence between Achievement Motivation on Learning Outcomes in SMA Negeri 25 Jakarta, this is evidenced by the significance value obtained greater than 0.05, greater than 0.05 (0.393> 0.05); (6) There is no indirect effect of the Quality of PJJ PJOK through Achievement Motivation on Learning Outcomes in SMA Negeri 25 Jakarta, this is evidenced by the beta coefficient value which is smaller than the beta coefficient which directly affects the quality of PJJ PJOK on learning outcomes of dribbling by 0.310 ( -0.02<0.310); (7) There is no indirect effect between Socioeconomic Conditions through Achievement Motivation on Learning Outcomes in SMA Negeri 25 Jakarta, this is evidenced by the beta coefficient value which is smaller than the beta coefficient value, the direct effect of Socioeconomic Conditions on Learning Outcomes of 0.062 (0.020 <0.062).Keywords: quality of PJJ PJOK, socio-economic conditions, achievement motivation, learning outcomes